Use of a Four-miRNA Panel as a Biomarker for the Diagnosis of Stomach Adenocarcinoma. (9th November 2020) - Chen, Xuan; Li, Xinji; Peng, Xiqi; Zhang, Chunduo; Liu, Kaihao; Huang, Guocheng; Lai, Yongqing
Abstract : Background . MicroRNAs (miRNAs) have been applied to cancer diagnosis taking into account their role in tumorigenesis. The main purpose of our study was to confirm the possibility of using miRNAs as noninvasive biomarkers for stomach adenocarcinoma (STAD) diagnosis. Methods . A total of 246 participants (130 STAD patients and 116 healthy controls (HCs)) were enrolled in this 3-phase study. Five STAD pools and 3 HC pools (with 4 participants in each pool) were used for the screening of the 28 miRNAs using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The training phase (30 STAD patients vs. 24 HCs) and validation phase (80 STAD patients vs. 80 HCs) were used to further verify the identity of these miRNAs. Kaplan–Meier survival analysis and bioinformatics analysis were also used. Results . The expression levels of miR-125b-5p and miR-196a-5p were upregulated in STAD serum, compared with the HCs, while miR-1-3p and miR-149-5p showed the opposite result. A four-serum miRNA panel was constructed, and the area under the receiver operating characteristic curve (AUC) was found to be 0.892 (95% CI: 0.834 to 0.936, sensitivity = 86.25 %, specificity = 78.75 % ). Only miR-125b-5p expression showed a significant difference between STAD patients and NCs in the survival analysis. The neurotrophin signaling pathway was associated with 4 miRNAs identified in STAD patients. Conclusion . The four-serum miRNA panel has great potential to be used as a noninvasive biomarker for STAD diagnosis.